Innovation across Europe: how important are institutional differences? - Barbosa, Natália (2011)
By changing the level of competition and/or affecting the allocation of resources, institutions can play a very important role on innovation activity. In this paper we investigate the relative importance of institutional variation across European countries in explaining differences in their innovation intensity at the industry level. We employ a novel indicator of innovation therefore circumventing the limitations of more traditional indicators. Our results are broadly consistent with previous empirical literature. They show that stringent product and labor market regulation affects innovation intensity negatively, and that more developed credit markets foster innovation. However, the empirical findings also raise doubts with respect to the strengthening of intellectual property rights as a means to stimulate innovation, a result that is in accordance with recent propositions in the literature.